CRISPR/Cas: An Emerging Toolbox for Engineering Virus Resistance in Plants - Xiaohui Zhan; Fengjuan Zhang; Ning Li; Kai Xu; Xiaodi Wang; Shenghua Gao; Yanxu Yin; Weiling Yuan; Weifang Chen; Zhiyong Ren; Minghua Yao; Fei Wang (Plants)
Clustered regularly interspaced short palindromic repeats (CRISPR)/Cas have been recognized as powerful genome-editing tools in diverse eukaryotic species, including plants, and thus hold great promise for engineering virus resistance in plants. Nevertheless, further attention is required regarding various issues associated with applying new powerful technologies in the field. This mini-review focuses on the recent advances in using CRISPR/Cas9 and CRISPR/Cas13 systems to combat DNA and RNA viruses in plants. We explored the utility of CRISPR/Cas for targeting the viral genome and editing host susceptibility genes in plants. We also provide insights into the limitations and challenges of using CRISPR/Cas for plant virus interference and propose individual combinatorial solutions. In conclusion, CRISPR/Cas technology has the potential to offer innovative and highly efficient approaches for controlling viruses in important crops in the near future.